The Politics of Modernity: the Discourse of the Westphalian System toward the Native in Indonesia - Maliki, Musa; Prihatiningsih, Witanti (Indonesian Perspective, 2023)
Modernity is a large concept that can be found in many disciplines, such as philosophy, history, sociology, anthropology, political economy, and International Relations (IR). One of many significant infrastructures of modernity is the concept of nation-states, the definition of which can also be found in the aforesaid disciplines. This article will elaborate on the concept of modernity concerning relations between nation-states and non-nation-states such as native local communities in which rooted in those multi-disciplined courses. This article argues that imagined nation-states of the Westphalian system impose, imprison, and marginalize native communities from within. The birth of nation-states in the European Western discourse has created marginalization of native communities around the world. Using some examples of Indonesian natives, this article shows that modernity is political. The politics of modernity either instrumentalized or marginalized and forced the Indonesian natives to obey the standardization of the Indonesian Westphalian system. As a result, since the Dutch colonialization up to now, the Indonesian natives have not yet embraced full citizenship rights because they are marginalized, subjugated, and discriminated against politically, economically, and socially.